A novel small-molecule inhibitor of hepatitis C virus replication acts by suppressing signal transducer and activator of transcription 3. (8th April 2015) - Niu, Yuqiang; Si, Youhui; Li, Yan; Chi, Xiaojing; Li, Xiang; Liu, Xiuying; Li, Duan; Cheng, Min; Fan, Jingjing; Si, Shuyi; Yang, Wei
Abstract: Objectives: Hepatitis C virus (HCV) infects hepatocytes and causes liver damage. The aim of this study was to identify new classes of host-targeting anti-HCV compounds that may provide novel approaches for antiviral treatment regimens. Methods: Cell culture-derived HCV (HCVcc), replicons and pseudoparticles were used in combination with high-throughput screening, reporter gene assays and cytotoxicity and signalling pathway analyses. Results: A small-molecule inhibitor of HCV, N -(cyclopropyl(phenyl)methyl)thieno[2, 3- d ]pyrimidin-4-amine, designated IB-32, was identified by screening a compound library with a Jc1-luc HCVcc assay. By using various virus models, HCV replication was identified as the predominant step of IB-32's action. IB-32 inhibited HCVcc (genotype 2a) and HCV replicons (genotype 1b) at low nanomolar ranges (with IC50 s of 40 ± 8 and 100 ± 15 nM, respectively). IB-32 was found to be non-toxic when tested against a panel of human cell lines in vitro at the effective antiviral dose. Mechanistically, IB-32 strongly inhibited STAT3 (Tyr705) phosphorylation, a necessary cellular factor for HCV replication and a pivotal therapeutic target for multiple cancers. Furthermore, the inhibition of HCV replication by IB-32 was augmented in cells with STAT3 knockdown. In contrast, the inhibitory effect of IB-32 was attenuated in cells overexpressing a constitutively active form of STAT3. Conclusion: The results presented here identify a promising STAT3-targeting anti-HCV therapeutic candidate. This novel small molecule could be further optimized and developed for use as both an antiviral and an anti-cancer drug.